Synthesis and Antimicrobial Screening of Some Novel Pyrazoline Derivatives - Kundariya, D.S.; Rupala, R.G.; Patel, P.K. (Asian Journal of Chemistry, 2012)
A new series of methyl-4-(4,5-dihydro-5-[(Z)phenyl]-1H-pyrazol-3-yl)-2-methylbenzohydrazide were synthesized by cyclisization of chalcones, methyl 4-((E)-3-((Z)phenyl)acryloyl)-2- methylbenzoate with hydrazine hydrate in presence of basic media. The chalcones were synthesized starting from 4-acetyl-2-methylbenzoic acid in 2 step. The structures of the synthesized compounds have been established on the basis of physical and spectral data and are screened for antimicrobial activity. Some of them exhibited significant activity.